PERTANGGUNG JAWABAN PEMILIK HEWAN PELIHARAAN ANJING YANG MELUKAI ATAU MEMBAHAYAKAN JIWA ORANG LAIN - Yuri Prayoga A.; Erdianto Effendi; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Criminal law recognizes the principle of criminal responsibility. Ideally, regulationsthat uphold justice are not only burdensome to one party, be it the perpetrator or the victim.In this study, there are two main issues: First, what is criminal liability for dog owners whoendanger the lives of other people, second, what are the specific standards and ideas forappropriate sanctions for the future related to the problem of keeping dogs in the future.The objectives of this minithesis are: First, to solve the problem of criminal liabilityfor dog owners who endanger other people's lives. Second, To find specific standard answersand appropriate sanction ideas related to dog rearing problems in the future. The authorconducted research using normative juridical methods or literature studies.From the research results there are two main things that can be concluded. First, thecriminal liability of dog pet owners who endanger the lives of other people. In criminal law,the liability of pet owners who endanger the lives of others uses the rules on negligence.Whoever because of his fault (negligence) causes another person to die, shall be punished bya maximum imprisonment of five years or a maximum light imprisonment of one year. Second,specific standards and appropriate sanction ideas for the future related to keeping dogs in thefuture. Because there are no specific regulations related to keeping dogs, special standardsfor keeping dogs must be formulated, namely dog keeping permits, cages that are largeenough, chain ties according to the size of the pet dog, adequate and good care and feeding.Furthermore, the idea of the right sanction for the future in the case of a pet dog that killsanother person depends on the consequences caused by the dog. We also see the over capacityfactor of prisons in Indonesia. So the sanction does not have to be just imprisonment. Can bereplaced with a fine or imprisonment.The author's suggestion in this study, suggests the importance of socialization by theauthorities regarding the maintenance of good and correct dog pets in society. As we know,many Indonesian people are interested in keeping dangerous animals. Especially dogs as pets.Must remind each other in living everyday life. If there are our neighbors who keep dogs anddo not implement a security system that guarantees the safety of the owner and neighborsaround the house. Suggested that there is a need for special arrangements regarding themaintenance of dog pets in Law no. 41 of 2014 changes to Law no. 18 of 2009 concerningAnimal Husbandry and Health. Because there are no specific rules governing the maintenanceof dogs.Keywords: Criminal Liability-Pet Dogs-Special Standar